Psychological Safety and Organizational Communication in Improving Team Effectiveness: A Systematic Literature Review in Organizational Behavior Perspective - Vera Wahani; Nofry Frans (Journal of Creative Power and Ambition (JCPA), 2026)
Psychological safety and organizational communication are crucial factors in enhancing team effectiveness in a dynamic work environment. This study aims to analyze research trends, the role of psychological safety in supporting organizational communication, and to identify research gaps regarding the relationship between psychological safety, organizational communication, and team effectiveness. The method used is a Systematic Literature Review (SLR) with a PRISMA approach on 60 articles from the 2020–2025 period. The review results show that psychological safety acts as the foundation for effective organizational communication through communication openness, the courage to express opinions, knowledge sharing, and increased team collaboration. Open organizational communication and supportive leadership also strengthen psychological safety, thereby supporting team effectiveness. This study also found that previous research is still dominated by quantitative approaches and specific organizational contexts, indicating the need for further research across various sectors and modern work patterns.